GARLIC EXTRACT PHYTOSOME: PREPARATION AND PHYSICAL STABILITY - ELFIYANI, RAHMAH; RADJAB, NANIEK SETIADI; WIJAYA, ANISA NURUL (International Journal of Applied Pharmaceutics, 2024)
Objective: Allicin is one of the components contained in garlic extract (Allium sativum L) and can easily be decomposed. To improve the chemical stability of allicin, a garlic extract was formulated in a phytosome system. Phytosomes, which are colloidal systems, are susceptible to ostwald ripening, which can result in an increase in particle size distribution. Changes in the size distribution indicate that the system is physically unstable. The aimed of the study was to test the physical stability of the garlic extract phytosome stored at three different temperatures for four weeks. Methods: Garlic extract phytosomes (GEP) were prepared by the thin layer hydration method using garlic extract and lecithin at the same concentration of 4.5%. Furthermore, the phytosomes were stored at 4 °C, 25 °C, and 40 °C for four weeks. Every week, a physical evaluation was carried out (organoleptic, pH, density, particle size, polydispersity index, and zeta potential). The data obtained were analysed statistically using the Friedman test. Results: The phytosome’s organoleptic result showed separation at 4 °C and 40 °C, starting from the second week. The average particle size of phytosomes was 214.3 nm, the zeta potential value was -29.08 mV, and the polydispersity value was 0.46. The results of statistical analysis showed that the Asymp. Sig<0.05 indicated that the particle size, zeta potential, polydispersity index, pH values, and density were significantly different at each week and storage temperature. Conclusion: Conclusion based on study indicated a decrease in the physical stability of phytosomes, especially those stored at extreme temperatures (4 °C and 40 °C).